Genetic Study of Intracranial Aneurysms. Issue 3 (March 2015) - Yan, Junxia; Hitomi, Toshiaki; Takenaka, Katsunobu; Kato, Masayasu; Kobayashi, Hatasu; Okuda, Hiroko; Harada, Kouji H.; Koizumi, Akio
Abstract : Background and Purpose—: Rupture of intracranial aneurysms (IAs) causes subarachnoid hemorrhage, leading to immediate death or severe disability. Identification of the genetic factors involved is critical for disease prevention and treatment. We aimed to identify the susceptibility genes for IAs. Methods—: Exome sequencing was performed in 12 families with histories of multiple cases of IA (number of cases per family ≥3), with a total of 42 cases. Various filtering strategies were used to select the candidate variants. Replicate association studies of several candidate variants were performed in probands of 24 additional IA families and 426 sporadic IA cases. Functional analysis for the mutations was conducted. Results—: After sequencing and filtering, 78 variants were selected for the following reasons: allele frequencies of variants in 42 patients was significantly ( P <0.05) larger than expected; variants were completely shared by all patients with IA within ≥1 family; variants predicted damage to the structure or function of the protein by PolyPhen-2 (Polymorphism Phenotyping V2) and SIFT (Sorting Intolerance From Tolerant). We selected 10 variants from 9 genes ( GPR63, ADAMST15, MLL2, IL10RA, PAFAH2, THBD, IL11RA, FILIP1L, and ZNF222 ) to form 78 candidate variants by considering commonness in families, known disease genes, or ontology association with angiogenesis. Replicate association studies revealed that only p.E133Q in ADAMTS15 was aggregated in the familial IA cases (odds ratio, 5.96; 95% confidence interval, 2.40–14.82; P =0.0001; significant after the Bonferroni correction [ P =0.05/78=0.0006]). Silencing ADAMTS15 and overexpression of ADAMTS15 p.E133Q accelerated endothelial cell migration, suggesting that ADAMTS15 may have antiangiogenic activity. Conclusions—: ADAMTS15 is a candidate gene for IAs. Abstract : Supplemental Digital Content is available in the text.